2009
DOI: 10.1159/000238821
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Combination Therapy with Olmesartan and Azelnidipine in Murine Polycystic Kidneys

Abstract: Background: Some reports have discussed the synergic effects of angiotensin II receptor blockers and calcium channel blockers on vascular injury or microalbuminuria. The present study examined the effects of combination treatment with olmesartan and azelnidipine on polycystic kidney disease in a mouse model (DBA/2-FG pcy mouse) and its mechanisms. Methods: The mice were divided into the following groups: combination treatment (n = 21), olmesartan treatment alone (n = 23), azelnidipine treatment alone (n = 29) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…In a murine model of polycystic kidney disease, combination therapy with olemsartan and azelnidipine retarded cyst growth by reducing interstitial inflammation and oxidative stress (26). A crossover study of simvastatin in 10 normocholesterolaemic patients with ADPKD showed improvements in renal blood flow and endothelial function, actions that may involve known pleiotropic effects of statins including anti-inflammatory effects (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of polycystic kidney disease, combination therapy with olemsartan and azelnidipine retarded cyst growth by reducing interstitial inflammation and oxidative stress (26). A crossover study of simvastatin in 10 normocholesterolaemic patients with ADPKD showed improvements in renal blood flow and endothelial function, actions that may involve known pleiotropic effects of statins including anti-inflammatory effects (27).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the treatment may affect macrophage infiltration to the glomerulus, fibroblast accumulation in the glomerulus, mesangial activation, and podocyte differentiation [20]. Combination therapy protects against cyst enlargement in polycystic kidney disease by suppressing interstitial inflammation, fibrosis, and oxidative stress through upregulating eNOS expression during the course of the disease [21]. Taken together, the combination of OLM plus AZL provides additional cardiovascular protective effects on arterial stiffness resulting in an improvement in the CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this result could be the antioxidant action of OLM and AZN, which occurs by inducing superoxide dismutase activity in blood vessels 31) or by suppressing ROS production. [32][33][34][35][36][37][38][39][40][41] OLM is known to block angiotensin II induced superoxide production by reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. 42) In addition, AZN has reported to attenuate ROS production via suppression of NADPH oxidase in a manner similar to OLM, 19,32) and is a more potent antioxidant than any other dihydropyridine calcium antagonists because of its good liposolubility and vascular endothelial penetration.…”
Section: Discussionmentioning
confidence: 99%
“…9) Similar to these results, we found increased MCP-1 expression in the vehicle group and decreased expression in the OLM and AZN groups. Based on these findings, we considered that the antioxidant effects of OLM and AZN suppressed not only AIM expression but also MCP-1 expression; further, these drugs reduced the number of infiltrating macrophages, resulting in the inhibition of interstitial fibrosis [32][33][34][35][36][37][38][39][40][41] . Currently, it is not yet clarified which drug, OLM or AZN, is stronger on antioxidant effects, future studies comparing OLM and AZN are required to determine which of these is a stronger antioxidant.…”
Section: Discussionmentioning
confidence: 99%